CAGE16-3 Cruise Report: CAGE-PWC April Cruise to the western Svalbard margin - Rasmussen, Tine L.; Nielsen, Tove; Laier, Troels; Ezat, Mohamed; Meilland, Julie; Ofstad, Siri; Nystedt, Elina; Pecori, Evelyn (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
From the afternoon of April 22nd to the early morning of May 1st 2016, CAGE at the Department of Geology Uit, the Arctic University of Norway, arranged a scientific cruise aimed at investigating sediment cores and pore water, water masses, and planktonic faunas, at the western Svalbard margin and western Barents Sea slope, also visiting methane seep sites off Vestnesa Ridge, Prins Karls Forland (PKF) and in Storfjorden Trough on R/V “Helmer Hanssen”. Investigated areas were (in order of visiting sites on the cruise): PKF, Vestnesa Ridge, PKF again, Storfjorden Trough and Storfjorden. This cruise can be regarded as a continuance of the previous cruise February 8-15, 2016, where all seep sites at Vestnesa Ridge and PKF were abandoned because of bad weather conditions. In April we hope to reach Vestnesa and PKF to get the cores we missed in February. The scientific sampling was done within the framework of several ongoing projects at the Department of Geology, University of Tromsø: “CAGE -Centre for Arctic Gas hydrate, Environment and Climate”, in which the sub-projects Paleo-CIRCUS and “OA-Ocean Acidification” are included. A total of 10 gravity cores, 3 multinet casts and 14 CTD (conductivity-temperature-depth) casts were performed along the western Svalbard margin (Vestnesa and PKF). Data were also collected in Storfjorden Trough and Storfjorden, no brine overflow detected in April either. Chirp profiles and multibeam lines were acquired during transits and in small surveys at potential core sites over outer Vestnesa, PKF and in Storfjorden filling previous gaps in records from earlier cruises.